A parallel program model for execution time estimation - Antonyuk Valery А.; Mikheev, Nikita G. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2022)
Programs for general-purpose graphics processing units represented as kernels without indefinite loops are considered in this paper. Such kernels can be implemented by CUDA or OpenCL technologies, for example. For execution time estimation, various models of program execution are introduced: from very “naive” to more reliable. All models are presented in the form of matrix expressions in max-plus algebra.